The Comparison of Walking Performance in Cold and Warm Biologically Conditions in Physiology - Habibzadeh Nasim (International Physiology Journal, 2018)
Walking is the best possible exercise to promote fitness. However, ambient temperature has an impact on walking regimen and performing exercise in different biological conditions can be challenging tasks. For example, both cold and hot temperatures can impair walking performance. In fact, walking in different cold and warm ambient can be challenging physical activity. But suitable sport wears and drinks during walking performances can protect of the body in cold and warm conditions. In this relation, different cold and warm weathers although can challenge walking performance but they account for opportunities for body to adapt to the different seasonal conditions. Thus, performing regular walking in different cold and warm weathers can help individual to stay active as well as fit.
Keywords: Walking exercise